Effect of skin tone on the accuracy of hybrid and passive stereophotogrammetry. Issue 9 (September 2019) - Wesselius, T.S.; Verhulst, A.C.; Xi, T.; Ulrich, D.J.O.; Maal, T.J.J.
Summary: Background: Three-dimensional (3D) surface images acquired from stereophotogrammetry are increasingly being used to plan or evaluate treatment by plastic surgeons. Stereophotogrammetry exists in active, passive, and hybrid forms. Active and hybrid stereophotogrammetry are believed to capture darker surfaces more accurately than passive stereophotogrammetry. The purpose of this study was to investigate whether skin tone has a clinically relevant effect on the accuracy of hybrid and passive stereophotogrammetry. Materials and methods: Seven subjects with different skin tones were recruited. 3D-printed face and breast were spray-painted in six different colors, ranging from white to black. The skin tones and paint colors were objectified by measuring their melanin index. 3D photos of the subjects and 3D prints were acquired with hybrid and passive stereophotogrammetry. These 3D photos were matched with specialized software, and their geometric differences were calculated. Results: None of the 3D photos showed a clinically relevant mean inaccuracy. On the 3D prints, hybrid stereophotogrammetry resulted in a smaller standard deviation of the inaccuracies than passive stereophotogrammetry (0.20 ± 0.06 mm vs. 0.35 ± 0.07 mm, p < 0.001). Passive stereophotogrammetry yielded a correlation between the melanin index of the spray paint colors and the standard deviation of the inaccuracy (Pearson's R = 0.60, p = 0.04). On human subjects, no correlation or difference in standard deviation of the accuracy was found. Conclusion: Skin tone does not influence the accuracy of hybrid and passive 3D stereophotogrammetry in a clinically relevant way.